The Concept of the Poor in Islamic Fiqh and Its Relevance to Legal Aid - Aabdul Hamid; Muhibbuththabary Muhibbuththabary; Jabbar Sabil (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
The definition of the poor in Islamic jurisprudence encompasses various aspects in identifying individuals eligible to receive legal aid and social assistance such as social assistance (Bansos), Zakat, and the Family Hope Program (PKH), and also includes economic criteria and basic needs that must be met. This demonstrates the alignment between the principles of fiqh and contemporary social policies. This study is a prescriptive normative legal analysis; in analyzing legal materials, the researcher employs a legislative and comparative approach by drawing on references from the literature. Subsequently, the researcher analyzes these legal materials qualitatively, specifically through comparative data analysis methods, comparison is used to contrast fiqh and legislation regarding the fiqh-based definition of the poor and needy in relation to recipients of legal aid. The research findings indicate that: (1) Those currently classified as the poor and needy are individuals or families without access to steady employment; (2) The right to legal aid is actually just one aspect of access to justice. Access to justice means “being treated fairly under the law; if one is not treated fairly, one will not receive the rights to which one is entitled.” The consequence of the principle of equality before the law is that everyone has the right to be treated equally before the law, including the poor who face legal problems. (3) The principle of equality before the law is not interpreted merely as equality in the eyes of the law, but rather as equality of access to the legal system and justice.